Interpretation of the Genotype by Tissue Interactions of Four Genes (AFP1, CIRP, YB-1, and HMGB1) in Takifugu rubripes Under Different Low-Temperature Conditions - Wang, Xinan; Liu, Zhifeng; Ma, Aijun (Frontiers in Molecular Biosciences, 2022)
Background: The differential expression of the same gene in different tissues could be due to the genotype effect, tissue effect, and/or genotype × tissue interactions. However, the genetic mechanisms responsible for this differential expression have not been reported to date. Methods: Four resistance genes to low temperature, the genes for antifreeze protein (AFP), cold induced RNA binding protein (CIRP), high mobility group protein box-1 (HMGB1), and Y-box binding protein (YB-1), were measured by PCR in the liver, spleen, kidney, brain, heart, intestine, muscle, gonad, and skin of Takifugu rubripes cultured under different temperature conditions (18, 13, 8, and 5°C). Split- split-plot analysis of variance, additive main effects and multiplicative interaction (AMMI) and genotype main effects and genotype × environment interaction (GGE) biplot analysis were used to evaluate the effects of genotype × tissue interactions on gene expression. Results: The results of split- split-plot analysis of variance showed that water temperature has a significant effect on the expression of T. rubripes cold resistant genes, while tissue × gene interaction has a highly significant effect on it. AMMI analysis showed that the contributions of genotype, tissue, and genotype × tissue interactions to the total variation in gene expression followed two trends: (1) as temperature decreased, the gene effect increased gradually and the genotype × tissue interaction decreased gradually; (2) the gene effect at 18 and 13°C was significantly lower than that at 8 and 5°C, while the interaction at 18 and 13°C was significantly higher than that at 8 and 5°C. GGE analysis showed that: at all temperatures except 8°C, the expression rankings of all four genes were highly positively correlated in all tissues except muscle; the expression stability of the genes was the same at 18°C/13°C and at 8°C/5°C; and AFP1 showed the best expression and stability among the four genes. Conclusion: 8°C/5°C as the suitable temperature for such experiments for T. rubripes. Among the four antifreeze genes evaluated in this study, AFP1 had the best expression and stability.